2020
DOI: 10.3390/genes11101176
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Interaction Changes during the iPSC-NPC Model to Facilitate the Study of Biologically Significant Genes Involved in Differentiation

Abstract: Given the difficulties of obtaining diseased cells, differentiation of neurons from patient-specific human induced pluripotent stem cells (iPSCs) with neural progenitor cells (NPCs) as intermediate precursors is of great interest. While cellular and transcriptomic changes during the differentiation process have been tracked, little attention has been given to examining spatial re-organization, which has been revealed to control gene regulation in various cells. To address the regulatory mechanism by 3D chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, few studies have investigated the mechanism of action of endogenous induction of the expression of these factors in cells. In our previous studies, we examined changes in gene expression and various epigenetic states, such as histone modification, chromatin accessibility, and chromatin interactions, during the differentiation of iPSCs into NPCs [29,30]. We reanalyzed our data to identify the intrinsic factors that determine the differentiation of stem cells into neuronal cells by integrate them in more analytical methods.…”
Section: Identification Of Intrinsic Factors Driving Neuronal Differe...mentioning
confidence: 99%
“…However, few studies have investigated the mechanism of action of endogenous induction of the expression of these factors in cells. In our previous studies, we examined changes in gene expression and various epigenetic states, such as histone modification, chromatin accessibility, and chromatin interactions, during the differentiation of iPSCs into NPCs [29,30]. We reanalyzed our data to identify the intrinsic factors that determine the differentiation of stem cells into neuronal cells by integrate them in more analytical methods.…”
Section: Identification Of Intrinsic Factors Driving Neuronal Differe...mentioning
confidence: 99%
“…This technique has been successfully applied, for example, to monitor the changes in the 3D chromatin-structure that can take place during the in vitro process that differentiates iPSCs to NPCs both in mice and humans. The presence of differentially interacting regions in both cell types has been found, thus suggesting that spatial organization affects the gene regulation of both pluripotency maintenance and neuroectodermal differentiation as well as the transition from precursors to terminally differentiated neurons [ 78 , 79 ]. Chromosomal conformation changes during in vitro differentiation from NPCs to neurons or astrocytes revealed that the majority of these conformational plasticity changes (i) occur in genes that regulate neuronal connectivity and chromatin remodeling, (ii) are cell specific, and (iii) include interactions that are anchored in common variant sequences that confer a heritable risk for schizophrenia in neurons [ 80 ].…”
Section: Ngs In Experimental Modelling Of Nddsmentioning
confidence: 99%